2000
DOI: 10.1046/j.1464-5491.2000.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality in Type 2 diabetes mellitus

Abstract: Perinatal mortality in Type 2 DM is significantly increased, mainly owing to an excess of late fetal death. Maternal factors such as obesity may be important contributors to the high perinatal mortality. Women diagnosed with GDM who have unrecognized Type 2 DM are also at high risk, but perinatal mortality is low in women with milder degrees of glucose intolerance in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
3
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(122 citation statements)
references
References 20 publications
6
99
3
13
Order By: Relevance
“…In addition, the study indicated that the outcome was poorer if type 2 diabetes was diagnosed during pregnancy compared with before pregnancy (6). The prevalence of type 2 diabetes in pregnancy was the highest in non-Caucasian women, who had a nonsignificantly higher HbA 1c during pregnancy (3,4,6).The aims of the present study were to evaluate the frequency of maternal complications and serious adverse fetal outcome in a group of women with type 2 diabetes who gave birth between 1996 and 2001 and to compare the outcome in this group to the outcome in three other groups, namely a group of women with type 1 diabetes who gave birth at our clinic in the same period, the background population in the same period, and a group of women with type 2 diabetes who gave birth at our clinic during 1982-1990 (7). To our knowledge, this is the first report that compares outcome in pregnancies in a recent group of women with type 2 diabetes to a former group of women with type 2 diabetes.…”
mentioning
confidence: 99%
“…In addition, the study indicated that the outcome was poorer if type 2 diabetes was diagnosed during pregnancy compared with before pregnancy (6). The prevalence of type 2 diabetes in pregnancy was the highest in non-Caucasian women, who had a nonsignificantly higher HbA 1c during pregnancy (3,4,6).The aims of the present study were to evaluate the frequency of maternal complications and serious adverse fetal outcome in a group of women with type 2 diabetes who gave birth between 1996 and 2001 and to compare the outcome in this group to the outcome in three other groups, namely a group of women with type 1 diabetes who gave birth at our clinic in the same period, the background population in the same period, and a group of women with type 2 diabetes who gave birth at our clinic during 1982-1990 (7). To our knowledge, this is the first report that compares outcome in pregnancies in a recent group of women with type 2 diabetes to a former group of women with type 2 diabetes.…”
mentioning
confidence: 99%
“…After excluding women with undiagnosed pregestational diabetes, the risk of perinatal death in deliveries after 37 weeks in the insulin-treated group was no longer increased, although excess risk persisted in the non-insulin-treated group. Cundy et al reported that, after excluding newly diagnosed type 2 diabetes from the GDM group, the perinatal mortality rate was no longer increased [29]. The increased risk of perinatal mortality observed in the group of women with GDM treated exclusively by diet is more difficult to explain.…”
Section: Discussionmentioning
confidence: 99%
“…35% in women with type 1 diabetes) (26). Women with type 2 diabetes tend to be of lower socioeconomic status and include many ethnic minorities and new immigrants, making the challenges of preconception awareness and care more difficult (27). Diabetes outcomes are consistently worse in those of lower socioeconomic status (28,29), and the increased rates of serious outcomes in women may also be due to non-health care factors, such as poor nutrition and smoking.…”
Section: Discussionmentioning
confidence: 99%